2023
DOI: 10.1111/jnc.15900
|View full text |Cite
|
Sign up to set email alerts
|

Obesity during preclinical Alzheimer's disease development exacerbates brain metabolic decline

Abstract: Alzheimer's disease (AD) is the most common form of dementia. Obesity in middle age increases AD risk and severity, which is alarming given that obesity prevalence peaks at middle age and obesity rates are accelerating worldwide. Midlife, but not late‐life obesity increases AD risk, suggesting that this interaction is specific to preclinical AD. AD pathology begins in middle age, with accumulation of amyloid beta (Aβ), hyperphosphorylated tau, metabolic decline, and neuroinflammation occurring decades before c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 165 publications
(190 reference statements)
1
8
0
Order By: Relevance
“…Here we report acceleration of Aβ plaque deposition and neuronal loss by obesity which agrees with previous studies using non-varied diets of high-fat or HCHF in rodent models of AD (Knight et al, 2014; Lin et al, 2016; Nam et al, 2017, 2018a; Sah et al, 2017; Walker et al, 2017; Medrano-Jiménez et al, 2019; Rollins et al, 2019; Bracko et al, 2020; Robison et al, 2020; Mazzei et al, 2021; Anderson et al, 2023). Importantly, we made novel observations of obesity concurrently driving neuroprotective processes in presence of accelerated AD pathology, including increased myelin and reduced activation of non-plaque-associated microglia.…”
Section: Discussionsupporting
confidence: 92%
“…Here we report acceleration of Aβ plaque deposition and neuronal loss by obesity which agrees with previous studies using non-varied diets of high-fat or HCHF in rodent models of AD (Knight et al, 2014; Lin et al, 2016; Nam et al, 2017, 2018a; Sah et al, 2017; Walker et al, 2017; Medrano-Jiménez et al, 2019; Rollins et al, 2019; Bracko et al, 2020; Robison et al, 2020; Mazzei et al, 2021; Anderson et al, 2023). Importantly, we made novel observations of obesity concurrently driving neuroprotective processes in presence of accelerated AD pathology, including increased myelin and reduced activation of non-plaque-associated microglia.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the lack of genotype effect, obese TgAD rats had a trend of lower hippocampal glucose uptake compared to obese nTg rats. The larger attenuation of glucose uptake in TgAD rats parallels the observed compromise in spatial working memory in obese TgAD rats but not in nTg rats by Anderson (Anderson et al 2023). It is also worth noting that the body mass of male TgF344-AD rats at 6.5 months of age positively correlates with soluble Aβ 42 concentration (Anderson et al 2023), suggesting an increased risk of AD.…”
Section: Effect Of Hchf Diet-induced Obesity In Pre-symptomatic Admentioning
confidence: 68%
“…The attenuated glucose uptake was likely detrimental for maintaining brain function in both nTg and TgAD rats. The attenuation in glucose uptake might be due to ine cient uptake and utilization of glucose caused by dysregulation of mitochondrial and neurotransmission pathways, downregulation in ETC complexes I, III, IV, and V and attenuated expression of Slc16a3/MCT4 (monocarboxylate transporter 4) leading to compromised ATP synthesis, accelerated ROS generation, and altered glycolytic ux as observed by Anderson in 6.5-month-old TgF344-AD rats fed with Western diet (Anderson et al 2023). The lack of genotype effect is expected in light of minimal amyloid at 6 months of age in this model.…”
Section: Effect Of Hchf Diet-induced Obesity In Pre-symptomatic Admentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have linked obesity to cognitive decline, particularly in relation to Alzheimer's disease (AD) [2][3][4][5][6][7]. Notably, a recent study identified midlife obesity as one of the primary modifiable factors strongly correlated with Brain Sci.…”
Section: Introductionmentioning
confidence: 99%